Loss of Mitochondrial Control Impacts Renal Health - Srivastava, Swayam Prakash; Kanasaki, Keizo; Goodwin, Julie E. (Frontiers in Pharmacology, 2020)
Disruption of mitochondrial biosynthesis or in mitochondrial dynamics or loss of control over mitochondrial regulation leads to a significant alteration in fuel preference and metabolic shifts that potentially affect the health of kidney cells. Mitochondria regulate metabolic network which affect multiple cellular processes. Indeed, mitochondria have established themselves as a therapeutic target in several diseases. The importance of mitochondria in regulating pathogenesis of several diseases has been recognized, however, there is limited understanding of mitochondrial biology in kidney. This review highlights an overview of the mitochondrial dysfunctions in kidney diseases. We describe the importance of mitochondria, and mitochondrial sirtuins in regulation of renal metabolic shifts in diverse cells types, and loss of control leads to increased cell-to-cell transdifferenciation processes and myofibroblast-metabolic shifts, which affect pathophysiology of several kidney diseases. In addition, we examine the mitochondrial-targeted therapeutic agents that offers potential leads in combating kidney diseases.